2018
DOI: 10.3390/genes9120612
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor Stem Differences Contribute to Species-Specific Use of Yeast and Human tRNASer

Abstract: The molecular mechanisms of translation are highly conserved in all organisms indicative of a single evolutionary origin. This includes the molecular interactions of tRNAs with their cognate aminoacyl-tRNA synthetase, which must be precise to ensure the specificity of the process. For many tRNAs, the anticodon is a major component of the specificity. This is not the case for the aminoacylation of alanine and serine to their cognate tRNAs. Rather, aminoacylation relies on other features of the tRNA. For tRNASer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Another possibility is that Trm3-mediated position 4 methylation influences other processes of translation, such as translocation or aminoacylation. Indeed, in E. coli, 2'-O-ribose methylation within the acceptor stem can negatively influence translation [47], and some aminoacyl tRNA synthetases rely on tRNA features within the acceptor stem or variable loop region to determine tRNA identity for charging [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that Trm3-mediated position 4 methylation influences other processes of translation, such as translocation or aminoacylation. Indeed, in E. coli, 2'-O-ribose methylation within the acceptor stem can negatively influence translation [47], and some aminoacyl tRNA synthetases rely on tRNA features within the acceptor stem or variable loop region to determine tRNA identity for charging [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Um44 modification is thought to increase tRNA stability by maximizing base stacking and base interactions that promote the C3'-endo form (preferred for stability in thermophiles) of RNA [55]. Another role for Trm44-mediated Um44 modification could be linked to charging of tRNA Ser by seryl-tRNA synthetases, which rely on features within the acceptor stem and variable loop regions for recognition [48][49][50][51]. Thus, both stability and accurate tRNA Ser charging could be affected in trm44 mutants, producing sensitivity to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although Crick’s frozen accident hypothesis once envisioned a perfectly interpreted genetic code [19], recent studies have found that cells tolerate surprisingly high levels of amino acid misincorporation [20]. The next pair of featured articles [1,2] investigated biochemical mechanisms that regulate translation fidelity.…”
Section: Genetic Code Evolutionmentioning
confidence: 99%
“…Berg et al [1] provided the first detailed characterization of human tRNA Ser identity elements. These are the critical nucleotides that are essential for tRNA recognition by the cognate aminoacyl-tRNA synthetase and determine the serine accepting identity of this tRNA.…”
Section: Genetic Code Evolutionmentioning
confidence: 99%
See 1 more Smart Citation